Anicare / Sathis Waran - Waran, Sathis (Universiti Teknologi MARA, Kedah, 2019)
Increasing pet owners and advance technologies have created a demand for the expertise and veterinarian across global recently. The Veterinary Services industry is currently growing drastically in the development of phase of its life cycle. Industry value added (IVA), which measures an industry’s contribution to the overall economy is expected to increase at the annualised rate of 3.3 % over the 10 years to 2023. In conjuction with this, the cost of veterinary care is also rising due to high demand for service. However, this has created a major setback for many customers. For instance, some customers claimed that the cost of dental scalling can up to RM850 which is expensive for them. Thus, we would like to introduce a new mobile application called “AniCare” which function similar to “Grab” concept to cater individual needs. Based on economy sharing concept, this mobile apps will help to not only help to reduce the cost of veterinary service but also creating more job opportunities among students.